The Impact of Negotiated Syllabus on Foreign Language Learners' Language Anxiety and Learning Motivation - Ali Pakdaman; Goudarz Alibakhshi; Abdollah Baradaran (Teaching English Language, 2022)
Negotiated syllabus, as a type of learner-centered syllabus, has been found to affect language learners' language achievement. This study aimed at investigating the foreign language learners' foreign language anxiety and motivation for learning. We selected two intact classes, consisting of 64 undergraduate language learners. We used a quasi-experimental research design. The two intact classes received foreign language anxiety and motivation scales before and after the treatment. The experimental group received a negotiated syllabus, while the control group received a teacher-developed syllabus. The two groups' scores on different aspects of motivation and language anxiety scales were analyzed through independent samples t-tests. The results indicated that while foreign language anxiety of learners in the experimental intact class significantly decreased, their motivation for learning English language increased. It was concluded that the use of negotiated syllabus can filter language anxiety and can significantly improve students' motivation for learning. Findings can be employed by English language teachers and learners.